Atlas of Minimally Invasive Surgery for Lung and Esophageal Cancer - Wang, Jun; K. Ferguson, Mark (Springer Netherlands : Imprint: Springer, 2017)
This Atlas presents a state-of-the-art review of VATS and robotic approaches to managing lung and esophageal cancers. It discusses cancer staging, physiological evaluation of patients, and patient selection for minimally invasive surgery. The atlas offers detailed descriptions of individual operations accompanied by anatomic drawings, intraoperative images, and 3-dimensional anatomic reconstructions. Written by recognized experts in the field, it provides readers with an unparalleled resource for advancing their skills in managing these cancers. It is a valuable reference work for thoracic surgeons in training as well as in practice who want to pursue minimally invasive surgery. It is unique in offering fully illustrated, step-by-step descriptions of the operative procedures.